Possession vs. direct play: evaluating tactical behavior in elite soccer - Kempe, M.; Vogelbein, M.; Memmert, D.; Nopp, S. (International Journal of Sports Science, 2014)
Measuring and evaluating tactical behavior is one of the main goals in performance analysis in professional soccer. A specific tactical approach may present the difference between winning and losing, especially in the highest level of competition. So fare tactical behavior is mostly determined by using one or two variables, like ball possession or number of passes. Within this study, we introduce a new index (Index of Offensive Behavior, IOB) that combines different variables of offensive actions to evaluate tactical behavior. To evaluate the indexes data of 676 official games (German Bundesliga 2009/10, & 2010/11, FIFA World Cup 2010) were analysed using the "MathBall"- notation software (Algorithma Ltd., 2009). IOB was able to reliable distinguish the two common tactical approaches in soccer: possession and direct play. Furthermore, we could show that successful teams prefer possession play and that game control (measured via Index of Game Control, IOC) is the most important variable of success irrespective of the tactical approach.